«Los rostros del personaje (Poesía 1994-2016)», de Francisco Gálvez (Castilla. Estudios de Literatura, 2019)
The publication of the gathered poetry of Francisco Gálvez, with the significant title of Los rostros del personaje, allows a re-reading of his creative trajectory, from his beginnings as co-founder of the Cordovan poetry review Antorcha de paja, emphasizing the setting and the development of some outstanding and recurrent motives, highlighted in some of the titles of his poems books and articulated now in the subtitle of this review.